Use of a 3D virtual app and academic performance in the study of the anatomy of the musculoskeletal system among Peruvian medical students - de La Barrera-Cantoni, Sol J. (2021)
Objective: To evaluate the association between the use of a 3D virtual App and academic performance among Peruvian medical students. In addition, factors associated with academic performance were also assessed. Methods: We conducted an analytical cross-sectional study in students enrolled in the Musculoskeletal System course during the first semester of 2019. Students filled out a data collection form and the "Self-directed learning readiness scale" (SDLRS) questionnaire adapted by Fisher, King, and Tangle. Linear regression models were carried out to assess the association between the appropriate use of the application and academic performance. Additionally, the factors associated with academic performance were evaluated using nested models, and beta coefficients were calculated by manual forward selection. Results: A total of 187 medical students were included. The 61% were female and the median age was 21 [20-22] years. The average grade was 13.5 +/- 2 and 21% reported an adequate use of a 3D App. No association was found between the use of the 3D App and academic performance in the adjusted model (a beta = 0.17; 95% CI: -0.45 to 0.80). We found that age (a beta = -0.22; 95% CI: -0.39 to -0.06), performing extracurricular activities (a beta = 0.75, 95% CI: 0.25 to 1.24) and having failed an anatomy/physiology course before (a beta = -2.11 to 95% CI: -2.9 to -1.8) were factors associated with academic performance. Conclusion: The adequate use of a 3D application to study the anatomy of the musculoskeletal system was not significantly associated with better academic performance.